The Role of Intraindividual Carotid Artery Variation in the Development of Atherosclerotic Carotid Artery Disease: A Literature Review - Shawn Stefan Albers; Andrew Stanton Kucey; Anish Engineer (University Library System, University of Pittsburgh, 2019)
Carotid artery disease (CAD) is associated with numerous risk factors, including hypertension, hyperlipidemia, hypercholesterolemia, diabetes mellitus, and smoking. These systemic risk factors do not affect the carotid arteries equally in most patients, resulting in asymmetrical bilateral and unilateral CAD. It is unclear if anatomic variations in the carotid arteries predispose an individual to formation of atherosclerotic CAD. We wanted to assess (1) the inter-individual or intra-individual anatomical variations in the carotid arteries and (2) whether anatomical variations predispose the development of atherosclerotic CAD. PubMed and Medline were utilized to identify relevant literature for critical appraisal, summarization and documentation. Inclusion and exclusion criteria were applied to narrow results and articles were critically appraised and analyzed. Evidence suggests that a low outflow/inflow ratio, elevated bifurcation height, and bifurcation angle are associated with increased risk for CAD. Sex and age demonstrated positive correlation with the disease. Additionally, tortuosity and kinking of the carotid arteries may affect the formation of CAD but coiling of the arteries is a natural age-dependent process and does not affect CAD development. This review suggests there are anatomic variations in the carotid arteries that increase the risk of developing carotid artery disease. The most significant risk factors include a low outflow/inflow ratio, increased internal carotid artery tortuosity, elevated bifurcation height, and bifurcation angle.